Microstructure and mechanical properties of composite cements: reactivity of pozzolanic and hydraulic cementitious materials - Gómez-Zamorano, L. Y.; Iñiguez-Sánchez, C. A.; Lothenbach, B. (Revista ALCONPAT, 2015)
This research was focused on the use of pozzolanic and hydraulic additions as partial replacement of Portland cement. In order to evaluate the mechanical properties, microstructure and hydration reactions of the composite cements phases, granulated blast furnace slag, fly ash, metakaolin, and geothermal silica were used as replacement materials. The following conditions were utilized: replacement levels of 50, 40 and 30% of the mentioned materials, a water/cementitious materials ratio of 0.4, curing temperatures of 20 and 50°C and curing intervals from 3 to 180 days. The results indicated a high degree of reactivity of replacement materials and an increase in the mechanical properties up to 200% compared to pure cement, resulting in a matrix of more dense reaction products and thus a reduction in porosity. Keywords: Microstructure, reactivity, mechanical properties, industrial byproducts.